PENGARUH PROFITABILITAS, KEBIJAKAN UTANG DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mellinda Lestari; Muthia Harnida (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2020)
The aim of this research is to analyze and obtain the empirical evidence of the effect of profitability, debt policy and dividend policy on firm value in Real Estate and Property companies listed on Indonesian Stock Exchange. This research is an explanatory research used the data of Real estate and Property Companies for the period of 2015 until 2017. The sampling technique used purposive sampling method. This sample taken in this study was 17 real estate and property companies. The total data analyzed in this study was 51 data. The data was analyzed using the multiple linier regression . The result of this research indicates that statistically profitability and dividend policy have significant effect on firm value , but debt policy have no significant effect of firm value of Real estate and Property companies listed on Indonesian Stock Exchange.